2015
DOI: 10.1371/journal.pone.0115635
|View full text |Cite
|
Sign up to set email alerts
|

WIP1 Phosphatase as a Potential Therapeutic Target in Neuroblastoma

Abstract: The wild-type p53-induced phosphatase 1 (WIP1) is a serine/threonine phosphatase that negatively regulates multiple proteins involved in DNA damage response including p53, CHK2, Histone H2AX, and ATM, and it has been shown to be overexpressed or amplified in human cancers including breast and ovarian cancers. We examined WIP1 mRNA levels across multiple tumor types and found the highest levels in breast cancer, leukemia, medulloblastoma and neuroblastoma. Neuroblastoma is an exclusively TP53 wild type tumor at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 46 publications
6
56
0
Order By: Relevance
“…Moreover, amplification of the PPM1D gene locus on 17q23 has been frequently reported in various cancers, including primary NB tumors21. Previous studies have shown that high expression of PPM1D predicts poor outcome in NB patients, which suggests PPM1D may play a critical role in the tumorigenesis of NB22 and therefore may have value as a therapeutic target in NB. Yet, the in vivo efficacy of Wip1 inhibitors is still poorly understood.…”
mentioning
confidence: 99%
“…Moreover, amplification of the PPM1D gene locus on 17q23 has been frequently reported in various cancers, including primary NB tumors21. Previous studies have shown that high expression of PPM1D predicts poor outcome in NB patients, which suggests PPM1D may play a critical role in the tumorigenesis of NB22 and therefore may have value as a therapeutic target in NB. Yet, the in vivo efficacy of Wip1 inhibitors is still poorly understood.…”
mentioning
confidence: 99%
“…In addition, a previous report demonstrated that Wip1 was significantly overexpressed in 56% of cancer tissues, and promoted tumor progression to a higher stage, poor prognosis and chemotherapy resistance (Table I) (32). Therefore, these data suggest that the inhibition of Wip1 expression levels may be a potential therapeutic target.…”
Section: Wip1 In Neuroblastomamentioning
confidence: 52%
“…Therefore, these data suggest that the inhibition of Wip1 expression levels may be a potential therapeutic target. GSK2830371 is a Wip1 selective antagonist able to significantly inhibit 96.5% of Wip1 activity in neuroblastoma cell lines, which promotes p53 function and apoptotic responses (32). Furthermore, GSK2830371 had a synergistic effect on the antiproliferative properties of the chemotherapeutic agents adriamycin and carboplatin (32).…”
Section: Wip1 In Neuroblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…Wip1 is encoded by protein phosphatase magnesium-dependent 1 Δ, which is located on the 17q22/24 human chromosomal region, and is a member of the protein phosphatase type 2C (PP2C) family. Previous studies have demonstrated that Wip1 is overexpressed in various types of cancer and that Wip1 is associated with cancer development, suggesting that this protein may be a tumor biomarker and therapeutic target (6)(7)(8)(9). However, the expression and role of Wip1 in bladder cancer have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%